2021
DOI: 10.1177/20543581211046077
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Comparative Efficacy between Sodium Bicarbonate and Heparin as A Locking Solution for Tunneled Central Venous Catheters Among Patients Requiring Maintenance Hemodialysis

Abstract: Background: Sodium bicarbonate (NaHCO3) is one of the promising solutions that has good safety profile and theoretical advantages regarding antimicrobial and antithrombotic properties but there are still limited reports. Objective: To compare the efficacy in lowering rate of catheter loss due to catheter-related thrombosis (CRT) or catheter-related blood stream infection (CRBSI) between sodium bicarbonate and heparin lock in prevalent chronic hemodialysis (HD) patients. Design: A multicenter, randomized, open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…None of the patients had any reported adverse events on SBLT. This is noteworthy, as a recent randomized controlled trial in adults on hemodialysis treated with SBLT was stopped early due to concern for CRT (20). However, the investigators in this study comment that the use of 7.5% SBLT (rather than 8.4%) and a higher proportion of patients with diabetes in the intervention arm explained the increased CRT rate.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients had any reported adverse events on SBLT. This is noteworthy, as a recent randomized controlled trial in adults on hemodialysis treated with SBLT was stopped early due to concern for CRT (20). However, the investigators in this study comment that the use of 7.5% SBLT (rather than 8.4%) and a higher proportion of patients with diabetes in the intervention arm explained the increased CRT rate.…”
Section: Discussionmentioning
confidence: 99%
“…An RCT showed that the incidence of catheter removal due to thrombosis (CRT) in the sodium bicarbonate group was higher than that in the heparin group, whereas the incidence of CRBSI and ESI was lower in the sodium bicarbonate group. Sodium bicarbonate is considered an alternative catheter lock used in every HD session with rt-PA every 3 weeks, especially when heparin is prohibited [ 118 ].…”
Section: Methodsmentioning
confidence: 99%